By book or by crook : a lighthouse library mystery - Gates, Eva, 1951- (Gates, Eva, 1951- Lighthouse library mystery., 2015)
Seriously determined to rewrite her life, Lucy, leaving her job poring over the rare tomes of literature for the Harvard Library behind, arrives in the Outer Banks where she lands a librarian job at the lighthouse library that seems like a dream come true until theft and murder enter the picture.